Arterial endothelial dysfunction and its role for prognosis assessment in cardiovascular patients - G. N. Soboleva; V. K. Fedulov; Yu. A. Karpov (Кардиоваскулярная терапия и профилактика)
The review presents the results of some large-scale clinical trials on the prognostic value of endothelial dysfunction, as a predictor of cardiovascular events. Coronary endothelial function, assessed invasively, is an independent predictor of spontaneous cardiovascular events, such as sudden cardiac death, myocardial infarction and cerebrovascular events, even after adjustment for pre-existing coronary heart disease (CHD) and other cardiovascular risk factors. Other studies demonstrated that coronary endothelial dysfunction is the strongest predictor of cerebrovascular events. Preoperative non-invasive assessment of endothelial function could independently predict postoperative cardiovascular and cerebrovascular events.